2013
DOI: 10.1111/age.12022
|View full text |Cite
|
Sign up to set email alerts
|

Paternal origins of Chinese cattle

Abstract: To determine the genetic diversity and paternal origin of Chinese cattle, 302 males from 16 Chinese native cattle breeds as well as 30 Holstein males and four Burma males as controls were analysed using four Y-SNPs and two Y-STRs. In Chinese bulls, the taurine Y1 and Y2 haplogroups and indicine Y3 haplogroup were detected in seven, 172 and 123 individuals respectively, and these frequencies varied among the Chinese cattle breeds examined. Y2 dominates in northern China (91.4%), and Y3 dominates in southern Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Mixing with the taurine cattle from the north generated a genetic North-South gradient of zebu-taurine mtDNA [71] and Y-chromosomal DNA [72]. In South China admixture of bibovine cattle (banteng, gaur or gayal) occurred, which may have been the dominant cattle species until 4500 BP [40,46].…”
Section: Early Zebu Dispersalmentioning
confidence: 99%
“…Mixing with the taurine cattle from the north generated a genetic North-South gradient of zebu-taurine mtDNA [71] and Y-chromosomal DNA [72]. In South China admixture of bibovine cattle (banteng, gaur or gayal) occurred, which may have been the dominant cattle species until 4500 BP [40,46].…”
Section: Early Zebu Dispersalmentioning
confidence: 99%
“…According to Y-STR haplotype gene frequencies and other studies on cell and molecular levels (Li et al, 2013a) The geographical distribution of these Y-STR gene frequencies revealed a declining gradient of male indicine introgression from south towards north and east towards west in China. The highest frequency of taurine alleles (93.0%) was found in the breeds from the northern group, while the highest percentage of indicine alleles (93.0%) was observed in the southern cattle populations.…”
Section: Y-str Haplotype Geographical Distribution In Chinese Cattle mentioning
confidence: 93%
“…According to the Chinese Cattle Breed Encyclopedia Record, at least 28 types of Chinese cattle have been identified as local fine breeds (Li et al, 2013a). In the last half century, many animal scientists were interested in understanding Chinese native cattle genetic construction, origin, and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In an initial survey of Chinese cattle breeds/populations, Y2 and Y3 were found to be dominant in northern and southern China respectively and central China was an admixture zone with Y2 predominating overall (Li et al . ; Zhang et al . ; Yue et al .…”
Section: Y‐chromosome Haplotypes and Diversity (H±sd) Of 34 Chinese Cmentioning
confidence: 99%
“…Here, we present a survey of Y‐haplotype data from 908 Chinese cattle males, incorporating data from previous reports (Li et al . ), to obtain a more precise estimation of haplotype diversity within each breed and to investigate paternal genetic origins of Chinese cattle.…”
Section: Y‐chromosome Haplotypes and Diversity (H±sd) Of 34 Chinese Cmentioning
confidence: 99%